Rancang Bangun Powder Pass Machine Menggunakan Sistem Kontrol Inverter - Avicena Pambudi, Javandish; Arif Cahyono, Muhammad Ridwan; Suharyanti (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
Construction of a powder pass machine with an inverter control system to enhance the efficiency of powder application in cable production. The machine is designed to evenly distribute powder onto cables, using a 3-phase AC motor controlled by a Toshiba VF-S15 inverter to regulate the rotation speed. The tool's design includes a frame made of UNP steel, a screw conveyor, and a control system with a selector switch, pilot lamp, and potentiometer. The manufacturing process involves utilizing existing materials in the factory and installing electronic components such as MCB and inverter. Testing was conducted on the IS-17 machine at PT XYZ, cable production department, to ensure the machine operates according to specifications and achieves the desired results. The results demonstrate that the machine efficiently and consistently distributes powder, improving the quality of cable production.